Antithrombotic thrombocytes: ectopic expression of urokinase-type plasminogen activator in platelets - Kufrin, Dubravka; Eslin, Donald; Bdeir, Khalil; Murciano, Juan Carlos; Kuo, Alice; Kowalska, M. Anna; Degen, Jay L.; Sachais, Bruce S.; Cines, Douglas B.; Poncz, Mortimer (My University, 2003)
Arterial occlusive disorders are a leading cause of human morbidity. We hypothesized that ectopic expression of fibrinolytic proteins in platelets could be used to favorably alter the hemostatic balance at sites of thrombosis. To test our hypothesis, we directed murine urokinase-type plasminogen activator transgene expression to platelets using a platelet factor 4 promoter. Urokinase was selectively expressed and stored in the platelets of these mice. These transgenic mice had altered platelet biology and a bleeding diathesis similar to that seen in patients with Quebec platelet disorder, affirming the role of ectopic urokinase expression as the etiology of this inherited disease. These mice were resistant to the development of occlusive carotid artery thrombosis in the absence of systemic fibrinolysis and displayed rapid resolution of pulmonary emboli. Moreover, transfusion of urokinase-expressing platelets into wild-type mice prevented formation of occlusive arterial thrombi. These studies show the feasibility of delivering fibrinolytic agents to sites of incipient thrombus formation through selective storage in platelets and offer a new strategy to prevent thrombosis and hemorrhage.